Speech accommodation strategies in the selling of life insurance - Ishak, Wan Irham; Rafik-Galea, Shameem (Universiti Putra Malaysia Press, 2015)
This paper explores the oral communication behaviour of speakers involved in life insurance sales meetings. It is often argued that speakers adjust their speech to “accommodate” the person they are addressing. This situation may be more prominent in sales talk, which is acknowledged as goal-orientated interaction with a specific structure, roles and patterns of language use. Using the communication accommodation theory (CAT), the authors attempt to show that the sellers (life insurance agents) and buyers (also known as prospects) of life insurance will use different accommodation strategies to ensure a sale or to reject a sale. Analysis of data from sales meetings provides some insights into the discourse of life insurance sales meeting conversations and management, including employment of accommodation strategies in the sales meetings. This paper addresses the role of speech accommodation by sellers and buyers of life insurance as seen in two life insurance sales meetings conducted in a specific region of Malaysia. The participants of the meetings were bilingual speakers of Malay, English and Chinese, and the competency level of spoken English differed from one participant to the other. The paper discusses the extent to which the participants used convergent and divergent strategies throughout the meetings to accommodate linguistic differences and difficulties, including the extent to which both the sellers and buyers of the life insurance were aware of the need to adjust their language according to the needs of their listeners in order to achieve the communicative purpose.